High Expression of PR-A and Low Expression of PR-B is Correlated with Inflammation in Endometrioma Cases - Yuane, Erick; Dewanto, Agung; Widad, Shofwal (The Indonesian Biomedical Journal, 2023)
BACKGROUND: Progestin therapy has been commonly used in endometriosis. The regulation of progesterone receptors B (PR-B) greatly affects the success rate of therapy in cases of endometriosis. The presence of tumor necrosis factor (TNF)-a in endometriosis triggers PR-B hypermethylation, decreasing PR-B expression and PR-B/A ratio that induce progesterone resistance. It may also occur in endometrioma. Studies regarding the distribution of PR-A and PR-B with TNF-a expression in endometriosis with endometrioma tissue samples has not been elucidated well. Therefore, this study was conducted to measure and compare the distribution of PR-A and PR-B expression, and to assess the effect of PR-B/A ratio on TNF-a in endometrioma and benign cysts.METHODS: A cross-sectional study was conducted by collecting paraffin blocks of endometriomas and benign cysts as controls, from patients undergoing surgery at Dr. Sardjito Hospital, Yogyakarta. Immunohistochemistry was performed to assess the expressions of PR-A, PR-B, TNF-a and PR-B/A ratio, to compared differences between endometriomas and benign cysts.RESULTS: Twenty-three endometrioma and 22 benign cyst tissue samples were collected. The mean PR-B expression and PR-B/A ratio were found to be lower in endometriomas than benign cysts, and mean expression of PR-A and TNF-a in endometriomas was higher than in benign cysts. However, there were no significant correlations between the expression of PR-A, PR-B, PR-B/A ratio, and TNF-a with endometriosis severity.CONCLUSION: In endometrioma cases, the expression of PR-A and TNF-a was higher, while the expression of PR-B and PR-B/A ratio was lower. However, there was no significant relationship between the ratio of PR-B/A and TNF-a.KEYWORDS: progesterone receptor, tumor necrosis factor-alpha, endometriosis, endometrioma, benign cyst, ovarian cyst